1992
DOI: 10.1111/j.1751-1097.1992.tb02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Interphotoreceptor Retinoid‐binding Protein and Α‐tocopherol Preserve the Isomeric and Oxidation State of Retinol

Abstract: Retinol decomposes rapidly into a number of products, including its aldehyde form, retinal, when introduced into buffer in phospholipid vesicles or ethanol. Interphotoreceptor retinoid-binding protein at low concentrations is found to protect retinol from isomerization and oxidation. The addition of alpha-tocopherol to either liposomes or an ethanolic-buffer solution also prevents decomposition. Neither of these agents interferes with the successful regeneration of pigment with 9-cis retinal in rod outer segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 18 publications
2
65
0
Order By: Relevance
“…In this connection, Crouch et al (1992) made the interesting observation that IRBP has significant activity in preserving the isomeric and oxidation state of retinol. The mechanism of this activity is not known.…”
Section: Transgenic and Knock-out Mouse Modelsmentioning
confidence: 99%
“…In this connection, Crouch et al (1992) made the interesting observation that IRBP has significant activity in preserving the isomeric and oxidation state of retinol. The mechanism of this activity is not known.…”
Section: Transgenic and Knock-out Mouse Modelsmentioning
confidence: 99%
“…11-cis retinal, again transported by IRBP, crosses the sub-retinal space and re-enters the photoreceptors (Ala-Laurila et al, Crouch et al, 1992;Wu et al, 2007). Once inside the outer segment it is transported back into the disc membrane, and the newly generated 11-cis retinal can re-bind opsin -a functional visual pigment has been regenerated.…”
Section: Figure 9 Images From a Patient With Fundus Albipunctatus (Rmentioning
confidence: 99%
“…IRBP, which is a 140-kDa glycoprotein and is the major soluble protein component of the IPM, is known to bind various isomeric and chemical forms of retinoids as well as long chain fatty acids (3,4). Participation of this protein in shuttling of retinoids in the IPM has been implied by the observations that its retinoid content is modulated by light (5) and that binding of retinoids to IRBP stabilizes them against degradation (6,7). It was also reported that IRBP can take up 11-cis-retinal from RPE (8 -10) and that it can efficiently deliver 11-cis-retinal to bleached ROS (11,12).…”
mentioning
confidence: 98%